Advances in Magnetic Two Dimensional Materials - Xiaoxi Li; Bo Li (Magnetochemistry)
Since the discovery of graphene in 2004, two-dimensional (2D) van der Waals (vdW) layered materials have attracted extensive attention for their great potential for application in the electronic, optoelectronic, and electrochemical fields [...]